Effects of nutrition and Bacillus amyloliquefaciens on tomato (Solanum lycopersicum L.) growing in perlite - Gul, A.=700 1 Kidoglu, F.; Tuzel, Y; Tuzel, H.
(Es, En)
Ilus., 37 ref.
Keywords: LYCOPERSICON ESCULENTUM; BACTERIA; RIZOSFERA; NUTRIENTES; ESTIMULANES DEL CRECIMIENTO VEGETAL; CULTIVO HIDROPONICO; ESPAÑA; BACILLUS AMYLOLIQUEFACIENS; SPANISH JOURNAL OF AGRICULTURAL RESEARCH